2018
DOI: 10.3389/fnins.2018.00225
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Olfactory Function With High Frequency Non-invasive Auricular Electrostimulation in Healthy Humans

Abstract: In past literature on animal models, invasive vagal nerve stimulation using high frequencies has shown to be effective at modulating the activity of the olfactory bulb (OB). Recent advances in invasive vagal nerve stimulation in humans, despite previous findings in animal models, used low frequency stimulation and found no effect on the olfactory functioning. The present article aimed to test potential effects of non-invasive, high and low frequency vagal nerve stimulation in humans, with supplementary explora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 109 publications
1
17
0
Order By: Relevance
“…Vagal effects on olfaction have been previously demonstrated in both animal and human studies. Indeed, stimulation of the vagus nerve has been shown to improve olfactory functioning in both animals and humans . By contrast, vagal injuries can cause temporal sensory deficits for up to 12 months (both gustatory and olfactory), as observed by Harris and Griffin in patients who underwent oesophagectomies or subtotal/total gastrectomies.…”
Section: Resultsmentioning
confidence: 99%
“…Vagal effects on olfaction have been previously demonstrated in both animal and human studies. Indeed, stimulation of the vagus nerve has been shown to improve olfactory functioning in both animals and humans . By contrast, vagal injuries can cause temporal sensory deficits for up to 12 months (both gustatory and olfactory), as observed by Harris and Griffin in patients who underwent oesophagectomies or subtotal/total gastrectomies.…”
Section: Resultsmentioning
confidence: 99%
“…In the current literature, low frequency MNS has indicated several functions in regards to gastric mobility that includes accelerated gastric emptying of liquids and improved gastric slow-wave rhythmicity (Ouyang et al, 2002), effects absent after vagotomy (Noguchi and Hayashi, 1996; Xu et al, 2006). In a previous article by our group (Maharjan et al, 2018), non-invasive and high frequency auricular VN electrostimulation improved olfactory performance in the supra-threshold test. This indicated that high frequency, VN stimulation (VNS) can modulate olfactory function with its neural connections (Figure 5).…”
Section: Discussionmentioning
confidence: 77%
“…This is the first study that indicates that MNS under high frequency stimulation can suppress odor intensity ratings of specific concentrations of several odors in combination with the increased and simultaneous activation in the OFCs in both hemispheres. The previous study by our group (Maharjan et al, 2018) demonstrated that non-invasive high frequency (80 Hz) electrostimulation of the auricular VN can improve the performance of supra-threshold test in healthy, adult male participants. This improvement in supra-threshold olfactory function was also supported by a significant improvement of VWrSO 2 (%) in the NIRS recordings only in the right hemisphere (Maharjan et al, 2018).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations